The United States' first foreign trade zone Staten Island, City of New York, opened February 1, 1937 / / J. Rivolta. - Rivolta, Jack, 1890-, artist (NYC : Works Progress Administration Federal Art Project, 1937)
Poster for the City of New York Department of Docks, showing five ocean liners.